2014
DOI: 10.1158/1538-7445.am2014-lb-223
|View full text |Cite
|
Sign up to set email alerts
|

Abstract LB-223: Intratumoral heterogeneity and precise personalized therapy revealed by one patient panel in hepatocellular carcinoma

Abstract: Background: The diversity of cancer genome significantly influences drug response and impairs the discovery of biomarker for patient stratification. As important preclinical models, patient derived cell lines are widely used in drug discovery and biomarker screening, yet complicated by intratumoral heterogeneity. Methods: We created a One Patient Panel (OPP), that is, a set of cell lines (26 lines in this case) derived from tumor tissue from one hepatocellular carcinoma (HCC) patient, and system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Multiple therapeutic strategies have been conducted to improve the prognosis of cancer patients. For example, the precise, personalized therapy by one patient panel has been reported to provide a powerful platform for optimizing drug selection and biomarker discovery, which may speed up the emergence of precision therapeutic regimens [118]. Similarly, a case report demonstrated that the ITH introduces significant challenges in designing effective treatment strategies, and the better understanding of the ITH may provide a clinical befit for cancer patients [119].…”
Section: Therapeutic Strategies For Treating Lc With Elevated Ithmentioning
confidence: 99%
“…Multiple therapeutic strategies have been conducted to improve the prognosis of cancer patients. For example, the precise, personalized therapy by one patient panel has been reported to provide a powerful platform for optimizing drug selection and biomarker discovery, which may speed up the emergence of precision therapeutic regimens [118]. Similarly, a case report demonstrated that the ITH introduces significant challenges in designing effective treatment strategies, and the better understanding of the ITH may provide a clinical befit for cancer patients [119].…”
Section: Therapeutic Strategies For Treating Lc With Elevated Ithmentioning
confidence: 99%